The effect of transcranial direct current stimulation on the treatment of patients with cervical myofascial pain syndrome - Farid Rezaei Moghaddam; Zohre Rozati; Afsane Dadarkhah; Kamran Azma; Siroos Azizi (فصلنامه ابن سینا, 2018)
Background: Myofascial pain syndrome (MPS) is one of the most common non-articular musculoskeletal pains. According to the previous investigations, the stimulation of brain's motor cortex is effective in reducing pain in patients who are resistant to treatment. The transcranial direct current stimulation (tDCS) is applied as a non-invasive method on the treatment of these patients. The aim of present study was to investigate the effect of tDCS on the treatment of patients with cervical myofascial pain syndrome. Materials and methods: In this randomized controlled clinical trial, the patients were randomly selected and assigned into two groups: tDCS and sham-tDCS (control) on primary motor cortex (M1) following standard treatment for 10 sessions. The main outcomes including pain intensity with visual analogue scale (VAS), pressure pain threshold, neck and shoulder range of motion, and neck disability index have been measured and compared between two groups before and immediately after the end of treatment sessions, and also at four and eight weeks follow-up. Results: The VAS scores before, immediately after, and at 8-week after the treatment were 5.3, 2.7, and 3.7 in tDCS group, and 5, 3.5, and 3.8 in control group, respectively (p=0.001). Neck disability index before, immediately after, and at 8-week after the treatment were 16.9, 6.7, and 8.4 in tDCS group, and 18.8, 9.9, and 13 in control group, respectively (p=0.0001). Pressure pain threshold and neck and shoulder range of motion showed a significant level. There were no significant differences between two groups. Conclusion: Application of trans-cranial direct current stimulation did not show a significant effect on improvement of pain and disability in patients with myofascial pain syndrome. Further investigation regarding comparison of tDCS and other methods is highly recommended on the treatment of myofascial pain syndrome.